New scientific methods to investigate library branch - N. A. Mazov; V. N. Gurejev (Библиосфера)
The operational experience of two scientific organizations with records on publications of employees in databases Web of Science (WoS), Scopus and Russian Science Citation Index (SRSCI). The attention is paid to own developments on application of the raw data taken from these DB, allowing in the automated mode to trace operatively the basic bibliometric indicators on a concrete person and organisation as a whole.